1997
DOI: 10.1038/386847a0
|View full text |Cite
|
Sign up to set email alerts
|

Dodecamer repeat expansion in cystatin B gene in progressive myoclonus epilepsy

Abstract: Progressive myoclonus epilepsy of the Unverricht-Lundborg type (EPM1; MIM 254800) is an autosomal recessive disorder with onset between 6 and 13 years followed by variable progression to mental deterioration and cerebellar ataxia. It is a rare disorder but more common in Finland (1 in 20,000) and the western Mediterranean. Two point mutations in the cysteine proteinase inhibitor gene cystatin B (CSTB), proved that this gene is responsible for EPM1 (ref. 3). An extensive search in the CSTB gene revealed mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
240
1
4

Year Published

1998
1998
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(253 citation statements)
references
References 29 publications
8
240
1
4
Order By: Relevance
“…A candidate-gene approach to positional cloning identified alteration of the cystatin B (CSTB) gene as the cause of EPM1. In addition to missense point mutations in the coding region, Lalioti et al (1997) and Lafreniere et al (1997) found expansion of a 12-nucleotide repeat located about 70 bp upstream of the transcription start site in the majority of EPM1 alleles, and also revealed that expansion of this VNTR reduced levels of CSTB mRNA in blood. Meloni et al (1998) provided further evidence that minisatellites can play significant roles in the regulation of transcription when they reported that a polymorphic tetranucleotide repeat in an intron of the tyrosine hydroxylase gene functions as an enhancer element.…”
Section: Vntrs As Transcriptional Regulatorsmentioning
confidence: 99%
“…A candidate-gene approach to positional cloning identified alteration of the cystatin B (CSTB) gene as the cause of EPM1. In addition to missense point mutations in the coding region, Lalioti et al (1997) and Lafreniere et al (1997) found expansion of a 12-nucleotide repeat located about 70 bp upstream of the transcription start site in the majority of EPM1 alleles, and also revealed that expansion of this VNTR reduced levels of CSTB mRNA in blood. Meloni et al (1998) provided further evidence that minisatellites can play significant roles in the regulation of transcription when they reported that a polymorphic tetranucleotide repeat in an intron of the tyrosine hydroxylase gene functions as an enhancer element.…”
Section: Vntrs As Transcriptional Regulatorsmentioning
confidence: 99%
“…The results revealed that the relative orientations of two GAA⅐TTC repeat tracts had no influence on the recombination frequency. 2 Thus, the inhibition of recombination between oppositely oriented tracts appears to be a (CTG⅐CAG) triplet repeat-dependent phenomenon (see "Discussion"). Nevertheless, when the tracts were in opposite orientations, the apparent recombination frequency was the highest when the (CTG⅐CAG) 98 repeats in the replicating plasmid (the pBR322 derivative) were in orientation II (Table III).…”
Section: Table II Plasmids Used In This Studymentioning
confidence: 99%
“…32 These examples are associated with an increased risk of insulin-dependent diabetes and several cancers, respectively. The palindromic sequence GGGCTAGCCC present in each repeat of the TFF2 intron suggests the existence of a functional DNA Figure 4 Evolutionary origin of the 25 TFF2 is most prominent in porcine pancreas, and is present in mouse and rat acinar cells of the pancreas, whereas it is not found in the human pancreas. 2,33 Although no direct relationship of TFF2 with a human disease is yet proven,TFF2 and TFF1 transcription is coordinately upregulated in some adenomas of stomach, pancreas, and biliary tract.…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of a GC-rich 12-bp repeat unit is responsible for a monogenic form of epilepsy termed EPM1. 25,34 This repeat, normally present in 2-3 copies in normal alleles of the promoter region of the gene encoding cystatin B is expanded to a large insertion (600-900 bp) leading to inhibition of transcription in affected patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation